The functional ability and health related quality of life of survivors of critical iliness after hospital discharge - Van Aartsen, Johannes (My University, 2016)
Background: Critically ill patients face physical, psychological, and health-related quality of life (HRQOL) problems. Factors relating to the intensive care unit (ICU) stay of a critically ill patient may affect a patient’s HRQOL after discharge from hospital and may include the development of acute respiratory distress syndrome (ARDS) and sepsis, prolonged length of mechanical ventilation (MV) and prolonged periods of immobility. Organ dysfunction and multiple organ failure (MOF) influence a patient’s QOL after hospital discharge. The presence of chronic diseases such as chronic obstructive pulmonary disease (COPD), diabetes mellitus (DM), and obesity may also contribute to the development of and severity of critical illness. Survivors of critical illness may be confronted with major problems during their recovery from critical illness. Limited South African data is available regarding the QOL of survivors of critical illness and limited research evidence is available to support rehabilitation services for this population after hospital discharge.The population of South Africa is a complex society and therefore has its own unique challenges that patients may face on a daily basis after a period of critical illness. These challenges may result in patients experiencing functional problems and a reduced HRQOL after critical illness. The aim of this study was to determine the functional ability and HRQOL of survivors of critical illness when assessed in the first six months after discharge from hospitals in South Gauteng. Methods: A prospective, observational, and longitudinal study was conducted using patients, who met the inclusion criteria for the study, in the ICU’s of a private hospital in Johannesburg. The acute physiology and chronic health evaluation II (APACHE II) and simplified acute physiology score II (SAPS II) were calculated and recorded for enrolled participants, as well as duration of MV, ICU length of stay (LOS) and hospital LOS. The physical function in ICU test scored (PFIT-s) was performed at the time of discharge from ICU and repeated at discharge from hospital. At one and six months after discharge from hospital, participants’ peripheral muscle strength was measured using a handheld dynamometer (HHD), exercise endurance was assessed using the six minute walking test (6MWT), and participants completed the short form 36 (SF-36) questionnaire, EuroQol Group 5 dimension (EQ-5D) questionnaire, patient health questionnaire (PHQ-9) and recent physical activity questionnaire (RPAQ). Results and Discussion: Twenty-four participants were enrolled into the study. The mean age was 51 (± 13.8) years, the majority were male (n=19, 79.2%), and most participants were employed (n=20, 83.3%) prior to the onset of critical illness. Half of the participants in this study presented with pre-existing disease prior to critical illness (n=12; 50%). Majority of participants underwent surgical interventions (n=19, 79.2%) which led to ICU admission and half of participants (n=12, 50%) reported having pre-morbid disease. All participants in the current study received physiotherapy treatment for the duration of their hospital stay. A significant change between mean PFIT-s interval scores (p=0.02) at ICU discharge and hospital discharge was found with a 0.4 points (± 0.7) change in interval scores. This change was not clinically significant, suggesting that not all the rehabilitation needs of these participants, who were recovering from critical illness, were met before their discharge from hospital. The increase in median 6MWT distance achieved was 65 meters, this being of clinical significance. There was no significant change in mean 6MWT distance achieved (53 meters ± 74.9).The limited mean distances that participants in this study were able to achieve during the 6MWT suggests that their endurance is impaired, which may impact their ability to perform activities of daily living. A marginally significant relationship was found between 6MWT distance at one month follow-up and SF-36 mental component score (MCS) at six months (p=0.05). Significant mean changes in peripheral muscle strength over six months after discharge were observed for right-sided (dominant side in all participants) elbow flexion (17.3 ±15.7, p=0.00), elbow extension (32.6 ± 37, p=0.02), hip abduction (53.4 ± 52.3, p=0.01), knee extension (59.9 ± 40.3, p=0.00), knee flexion (42.4 ± 31.3, p=0.00) and ankle dorsiflexion (29.9 ± 36.9, p=0.02), left-sided hip abduction (36.4 ± 45.2, p=0.02), knee flexion (40 ± 43.3, p=0.01), and ankle dorsiflexion (43.3 ± 48.1, p=0.03). The fact that majority of participants in this study lived alone may account for the improvements in muscle strength observed as they would be dependent on themselves for performing daily activities.The median PHQ-9 score showed an improvement of 2 points between one month and six months follow-up. A significant change in mean SF-36 physical component score (PCS) of 8.8 points (± 7.6, p=0.00) was observed over the six months period. This relates to improvements in the physical domain of HRQOL over the first six months after discharge from hospital following critical illness. The significant improvement in HRQOL related to PCS in the current study may be due to the fact that most participants lived alone and were self-dependent for daily activities even though they had some form of support from family and friends, and some of them had also returned to work by six months following discharge. Participants in the current study had several co-morbidities which may also have contributed to the lower observed mean PCS scores at six months. Significant changes in mean SF-36 domain scores were observed over six months for the role physical (RP) (p=0.00), bodily pain (BP) (p=0.05), general health (GH) (p=0.00), vitality (VT) (p=0.01) and the social functional (SF) (p=0.00). A significant mean change of 14.6 points (± 9.7) in EQ-5D visual analogue scale (VAS) scores was observed over six months after discharge. Participants’ abilities to mobilise, care for themselves and participate in usual activities (measured using the EQ-5D) improved over time as they continued to recover from critical illness. Large reduction in level of pain and discomfort experienced at six months as measured with the EQ-5D questionnaire may be due to wound healing that took place as the majority of participants underwent surgery. A significant relationship was found between the SF-36 PCS at one month follow-up and severity of illness (SAPS II) scores.Very weak and weak relationships were found between the SF-36 PCS and APACHE II scores (r=0.036) and SAPS II scores (r= 0.31) and moderate strength relationships were found between SF-36 PCS and PHQ-9 scores (r= -0.49) and 6MWT distance (r= 0.54) at six months follow-up. None of these relationships were statistically significant. Moderate strength negative relationships which were statistically significant, were identified between the SF-36 MCS and ICU LOS (r= -0.56; p=0.04) and hospital LOS (r= -0.56; p=0.04) at six month follow-up. A strong negative relationship was found between the SF-36 MCS at six months follow-up and duration of MV which was statistically significant (r= -0.7; p= 0.01). A strong negative relationship was found between SF-36 MCS scores and PHQ-9 scores at six months after discharge from hospital which was statistically significant (r= -0.72; p= 0.01). The main reasons reported by participants for not returning to work were pensioner status and physical weakness; however, at six months more than half of participants had returned to employment. The presence of depressive disorders did not directly influence return to work. The relatively good return to work rate observed may be attributed to the significant increases in muscle strength and PCS observed as well as the reduction in problems reported in relation to mobility, self-care, pain or discomfort and participation in usual activities over the first six months following discharge. Length of MV, SF-36 MCS and SF-36 PCS scores had no statistically significant relationship with exercise endurance at six months after hospital discharge. Limitations to this study include the small sample size and high drop-out rates. Conclusion: Survivors of critical illness in Gauteng province suffered from limitations in functional abilities at ICU discharge and improvements observed at hospital discharge were not clinically significant. Even though peripheral muscle strength improved significantly for participants in the six months following discharge, they still presented with limitations in exercise endurance. Significant improvements were observed in QOL related to physical functioning but little improvements were observed for QOL related to mental health. Some participants presented with symptoms of depression. More than half of participants returned to employment by six months following discharge. Findings from this study suggest that survivors of critical illness don’t recover fully on their own after an episode of acute illness. These results should be used to motivate for implementation of structured rehabilitation programmes, including counselling, to aid the physical, emotional and mental recovery of survivors of critical illness in the long term after hospital discharge.
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Physiotherapy Johannesburg, 2016
Keywords: Quality Of Life; Critical Illness; Patient Discharge; Intensive Care Units